Effects of traditional Chinese exercise on cardiac rehabilitation after percutaneous coronary intervention: study protocol for network meta-analysis of randomised controlled trials. Issue 2 (9th February 2019) - Luo, Chuanjin; Wen, Junmao; Sun, Weipeng; Li, Ting; Yu, Xiaojiang; Zhang, Tian; Zhou, Xiaoqi; Wu, Wei; Li, Rong
Abstract : Introduction: Coronary heart disease (CHD) is the most common cause of death worldwide. Percutaneous coronary intervention (PCI) has been shown to reduce mortality in patients with CHD. However, there are still recurrences of cardiovascular events after PCI. Cardiac rehabilitation (CR) in patients with established CHD is associated with reductions in cardiovascular mortality and hospital admissions, as well as improved quality of life. More and more clinical trials suggest that traditional Chinese exercise (TCE) plays a positive role in patients post-PCI. The primary purposes of the current study are to conduct a network meta-analysis of randomised trials to determine the effects of TCE in patients after PCI, and to separately compare the effects of tai chi, baduanjin and yijinjing on CR after PCI. Methods and analysis: Studies will be retrieved from the following databases: PubMed, Embase, Cochrane Library, Chinese National Knowledge Infrastructure, Wanfang Data, Chinese BioMedical Database and Chinese Science and Technology Periodicals Database, from inception to December 2018. We will include randomised controlled trials that are related to the effects of TCE therapies in patients after PCI. The primary outcomes will be all-cause mortality, revascularisations, health-related quality of life and hospitalisations. Two reviewers will independently select eligible articles. For each included article, two reviewers will independently extract the data and assess the risk of bias by using the Cochrane risk of bias tool. Bayesian network meta-analyses will be conducted to pool all treatment effects. The ranking probabilities for the optimal intervention of various treatments (tai chi, baduanjin or yijinjing) will be estimated by the mean ranks and surface under the cumulative ranking curve. The Grading of Recommendations Assessment, Development and Evaluation System will be used to assess the quality of evidence. Ethics and dissemination: The results will be disseminated through peer-reviewed publications. They will provide consolidated evidence to inform clinicians on the potential functions of TCE in CR, and to provide reliable evidence for the application of TCE. Trial registration number: CRD42018088415.